Increasing levels of Rumensin® in limit-fed, high energy, growing diets for beef steers and effects on subsequent finishing performance - Montgomery, Sean P.; Sindt, J.J.; Farran, T.B.; LaBrune, H.J.; Hunter, R.D.; Higgins, James J.; Nutsch, T.A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred sixty-four crossbred beef steers were used to determine optimal Rumensin ® concentrations in limit-fed, high-energy, growing diets. Diets contained 30, 40, or 50 grams of Rumensin per ton of dry matter (R30, R40, and R50). Average daily gain and feed efficiency during the growing phase were not different (P>.80) among treatments. Steers that received R50 in the growing phase had the highest average daily gains during the finishing phase (P<.05). This resulted in heavier carcass weights for R50 than R30 (P<.05) and R40 (P<.12). Feed efficiencies during the finishing phase were not different among treatments (P>.40).
Keywords: Beef; Rumensin; Limit feeding; Finishing cattle